Efektivitas Pengelolaan Laporan Kejadian Bencana Dalam Manajemen Rehabilitasi Di BPBD Kab. Karawang - Nurhaida, Karmelita; Arnu, Anggi Pasca (Peneliti.net, 2024)
This study aims to analyze the effectiveness of managing disaster incident reports in rehabilitation management at the Regional Disaster Management Agency (BPBD) Karawang Regency. Descriptive research methods were used in this study to describe and explain the process of managing disaster incident reports and rehabilitation management carried out by BPBD Karawang Regency. Primary data was obtained through observation, interviews, and document studies at the BPBD, while secondary data was obtained from related literature and statistical data. The results of the study show that BPBD Karawang Regency has made sufficient efforts in managing disaster incident reports and implementing rehabilitation management. However, there are still a number of obstacles and challenges that affect the effectiveness of report management and the rehabilitation process, such as limited resources, coordination between agencies that is not yet optimal, and a lack of community participation. In conclusion, BPBD Karawang Regency needs to improve the effectiveness of managing disaster incident reports through steps such as increasing coordination with related agencies, increasing public awareness, and optimizing the use of available resources. This research can be a reference for BPBD and related parties in improving disaster rehabilitation management in Karawang Regency